An IoT Technology as Smart Water Management System for Family Medicinal Plants - Muhammad Akmal Ar Rasid; Dendy K Pramudito; Amali (Jurnal Informatika Ekonomi Bisnis, 2026)
Watering of Family Medicinal Plants located in government institutions should not follow a regular interval. As they require adequate water to grow, over-watering can lead to wastage of water and can decrease efficiency in plant maintenance. The plants are typically watered by employees manually based on a schedule or by checking up on the plants. But, at times soil moisture can vary at any hour of the day and irrigation might not happen if a person is not available to check. There are chances of overwatering or underwatering the plants. In this paper we propose a system which uses Internet of Things to monitor the soil moisture level and make irrigation automated. NodeMCU ESP8,266 acts as the main controller of the system. A soil moisture sensor is used to sense the amount of water present in the medium where the plants are growing. A relay module is used to control the pump, a water pump is used to water the plants and finally an I2C LCD is used to display the real time information. We also use IoT Watering platform to display the monitoring data and control the system over internet. We performed field study, literature survey, requirement study, system design, implementation and testing of the prototype. The results showed that the system sensed the soil moisture levels and send the data to monitoring platform and display the data in real time. The water pump is used to water the plants automatically. If the moisture level falls below the threshold which is set in the system, the pump will switch on. If the moisture level is enough for the plants to survive, then the pump will switch off. This system allows us to have better control over watering of plants, measure the efficiency and make the process faster.